Harmonizing Global English: Fostering Cultural Acumen in English Language Teaching Textbooks from Teachers’ Perspectives in Nepal - Pitambar Paudel (Generasi Sains Indonesia, 2024)
The escalating prevalence of English on a global scale has precipitated a surge in its non-native speakers. This phenomenon, deeply intertwined with the forces of globalization, has engendered multifaceted transformations across domains such as science, technology, commerce, communication, and educational policies. The dissemination of English as a lingua franca evinces both advantageous and detrimental ramifications within non-native contexts, particularly in relation to the advocacy, preservation, and manifestation of indigenous languages. It is imperative that English language teaching (ELT) textbooks in non-native settings adopt a conscientious approach towards foregrounding local languages and cultures, recognizing culture as the matrix of beliefs and customs that underpin societal life and are articulated through language. Given the pivotal role of textbooks as primary conduits of knowledge and information across diverse cultural cohorts, the present inquiry endeavors to scrutinize the attitudes of English educators towards the treatment of English and cultural awareness within ELT materials. Employing an exploratory sequential research design, a cohort of 50 English instructors, uniformly utilizing a prescribed course book albeit hailing from disparate geographic locales, was purposefully selected through non-random sampling methodologies. Methodologically, a combination of semi-structured interviews and questionnaires served as instruments for data acquisition, which was subsequently subjected to both qualitative and quantitative analyses. Findings unveil a conspicuous inclusion of English varieties within the textbook corpus, yet discernible lacunae persist in the nuanced exploration of cultural awareness facets. The discerned lacunae in the nuanced exploration of cultural awareness facets within ELT textbooks underscore the imperative for curricular revisions and pedagogical enhancements aimed at fostering a more culturally sensitive and inclusive approach to English language education in non-native contexts.